Teaching Styles and Learning Motivation in Enhancing Futsal Dribbling Skills among Junior High School - Muh Imam Buhari; Poppy Elisano Arfanda; Muhammad Ishak (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mastery of dribbling is fundamental for successful futsal performance, yet traditional physical education often struggles with low student motivation and monotonous instruction. This study examined the main and interaction effects of teaching style (reciprocal vs. command) and learning motivation (high vs. low) on futsal dribbling outcomes among junior high school students. Utilizing a true-experimental 2×2 factorial design, 32 eighth-grade students were selected via cluster random sampling and underwent 12 instructional sessions. Motivation was measured using a validated Likert-scale questionnaire, while dribbling skills were evaluated via Nurhasan’s standardized test. Data were analyzed separately by gender using two-way ANOVA (alpha = 0.05). The findings revealed that the reciprocal style yielded significantly higher dribbling outcomes than the command style for both male (M = 88.20 vs. 86.30) and female students (M = 89.00 vs. 87.33). Crucially, a significant teaching style × motivation interaction was found for both sexes (male: F (1,16) = 13.83, p = .002; female: F (1,8) = 12.25, p = .008). The reciprocal style excelled for highly motivated students, whereas the command style was more effective for low-motivated students. These insights demonstrate that instructional effectiveness is highly contingent on student motivation, suggesting that educators should dynamically adapt teaching styles rather than applying a uniform approach.